1980
DOI: 10.1007/bf02408607
|View full text |Cite
|
Sign up to set email alerts
|

A microspectrophotometric analysis of the effect of fluoride on immature enamel matrix protein of rat molar teeth

Abstract: Over a 24-h period, Wistar rats from 4 litters, 6 to 9 days old, were given five intraperitoneal injections of a solution of 0.9% sodium chloride containing sodium fluoride (3 mg F/kg body weight). Within-litter controls were used. All rats were killed by decapitation 2 h after the final injection and the rat heads, cut sagittally, were processed for protein histochemistry. The intensity of staining of the protein in the enamel matrix of the upper jaw molar tooth buds was quantified using the two-wavelength me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Starting in 1975, a series of papers have shown that enamel of animals exposed to fluoride present increased amounts of protein or certain amino acids during the maturation stage (4)(5)(6)(7)(8). Later, in 1989, retention of immature proteins and decreased proteolysis in fluorotic rat enamel was described (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Starting in 1975, a series of papers have shown that enamel of animals exposed to fluoride present increased amounts of protein or certain amino acids during the maturation stage (4)(5)(6)(7)(8). Later, in 1989, retention of immature proteins and decreased proteolysis in fluorotic rat enamel was described (9,10).…”
Section: Introductionmentioning
confidence: 99%